Interactive structures visualizing structural behavior - Vassigh, Shahin (New York Wiley, 2005)
A learning tool that uses three-dimensional computer generated models, animations, audio narration, and interactive quizzes to communicate the fundamentals of structural behavior and analysis.--Disc container
Title from title screen.
CD ID MD02013A1, MD02013A2 & MD02013A3"--Disc surface
Computer with a processor running 120MHz or faster; at least 32 MB of total RAM installed on computer, 64 MB recommended; CD-ROM drive; Microsoft Windows or Mac OS X
Keywords: Structural analysis (Engineering) -- Interactive multimedia; Structural stability -- Interactive multimedia